ANALISIS KESALAHAN SISWA MENYELESAIKAN SOAL CERITA ARITMATIKA SOSIAL BERDASARKAN NEWMAN’S ERROR ANALYSIS DI SMP - Arumiseh, Neni Eka; Hartoyo, Agung; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research is to describe the students error in solving social arithmetic story problems based on Newman's Error Analysis (NEA) and describe the factors caused students error in solving social arithmetic material story problems based on Newman's Error Analysis (NEA) on seventh grade students of junior high school. The research method used is descriptive method in the from of case study research. The subjects of this research are 21 students. Data collection techniques used are test techniques and direct communication techniques (interviews). The results showed that the error which were done by students were error in reading (R), comprehension errors (C), transformation errors (T), process skills errors (P), end encoding errors (E). Casual factors that were done by students in each error in terms of cognitive are including students do not understand the problem as a whole, lack of mastery in the use of formulas and doing calculations, in a hurry in working on the problem, not careful, confusion factors in students, factors of forgetfulness and not good time management. Keywords: Error Analysis, Story Question, Social Arithmetic, Newman?s Error Analysis (NEA).